O-L06 The use of tumour marker Ca19.9 in the follow up of patients with resected biliary tract cancer: Results from the BILCAP randomised clinical trial. (16th December 2021) - Morrison-Jones, Victoria; Gao, Fangfei; Fletcher, Peter; Valle, Juan; James Garden, O; Cunningham, David; Bridgewater, John; Primrose, John
Abstract: Background: Even after resection biliary tract cancer has a poor outlook. Follow-up is commonly utalises and the sialyl-Lewis tetra saccharide antigen Ca19.9, a known tumour marker in pancreatic and biliary malignancy (upper limit of normal (ULN) 37U/ml). However, the evidence base for the utility of Ca19.9 is limited. The UK BILCAP trial examined the use of adjuvant capecitabine chemotherapy in resected biliary tract cancer and establishing a new global standard of care. Ca19.9 was regularly measured as part of the BILCAP protocol, this provides an opportunity to assess the use of this marker in a large trial with complete patient follow-up. Methods: Between March 2006 and December 2014 447 patients underwent resectional surgery (R0 or R1) then were randomised to receive capecitabine chemotherapy or observation. CT imaging and Ca19.9 were performed 3 monthly in year 1, 6 monthly in year 2, and annually thereafter up to 5 years. Follow up was continued until all patients had 5 years follow-up. Recurrence was based mainly on imaging criteria combined with the clinical presentation. The cohort was divided into progression and non- progression groups and the Ca19. 9 values recorded were investigated using descriptive analyses with cut-off of 37 (ULN), 100 and 400U/ml. Results: Of 447 study patients 440 had at least one Ca19.9 measurement from either post-operative baseline (394) or a follow-up visit (422). Baseline Ca19-9 was elevated above 37U/ml in 96 patients and 82 (85%) went on to develop recurrence. The sensitivity, specificity, positive predictive value (PPV) and negative predictive values (NPV) of the Ca19.9 on follow up are shown in the table. Conclusions: Although high Ca19.9 levels predict recurrence as shown by acceptable positive predictive values at cut-offs of 100 and 400U/ml the negative predictive values are very poor as most patients develop recurrence without elevation of Ca19.9. Ca19.9 measurement is of very limited value in the follow up of patients with resected biliary cancer.